Application of the chiral auxiliary [(eta(5)-C5H5)Fe(CO)(PPh(3))] to the stereoselective formation of 4-substituted-1,4-dihydronicotinoyl complexes - Beckett, R; Burgess, V; Davies, S; Krippner, G; Sutton, K; Whittaker, M (1996)
In solution regio-and stereoselective additions of nucleophiles to (RS)-[(η5-C5H5)Fe(CO) (PPh3)CO-3-pyridyl] (1) occur at C-4 to give the corresponding nitrogen-stabilised anions. Subsequent quenching of these anions by a proton, a chloroformate or dimethyl sulfate gives the corresponding 1,4-dihydropyridine complexes as single diastereoisomers. The predicted stereochemical course of the nucleophilic additions is confirmed by a single crystal X-ray structure determination of (Fe-RS,4-RS)-[(η5-C5H5)Fe(CO) (PPh3)CO-3-(N-methoxycarbonyl-4-methyl-1,4-dihydropyridyl)].